High Order Thinking skill ( HOTS Analisis Kemampuan Siswa Menyelesaikan Soal Ujian Nasional HOTS Mata Pelajran Fisika SMA 10 Kota Bengkulu - Sopiah; Anisa Auliya; Adli Ikhsan; Ahmad walid (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2019)
Abstract The 21st century is also known as the age of knowledge (knowledge age), in this era, all alternative efforts to meet the needs of life in various contexts are more knowledge based. In taxonomy, students' knowledge and skills can be measured by cognitive domains which include mental activities ranging from the lowest to the highest processes. Likewise, the National Physics exam questions are designed with high order thinking skill question models. For this reason, it is necessary to conduct an analysis of physics National Examination questions that have been designed with a high order thinking skill question model in SMA Negeri 10 Bengkulu city by looking at the results of evaluating student learning with the type of High Order thinking skill questions. In this study using the Research Method of physics questions by collecting data on national exam questions in the last three years. Based on research conducted the level of success of students completing national exam questions based on HOTS is still very low, it can be seen from the data we get that in SMAN 10 Bengkulu City the value of the physics national exam in 2018 has decreased from the previous year with the weight of LOW questions in 2017 totaling 11 pieces and in 2019 there were 18 questions.